Exploration of Factors That Influence Patients' Decisions in Choosing A Beauty Clinic: A Grounded Theory Approach - Uliyah, Dian Alfiyatul; Cahyono, Dwi; Hermawan, Haris (Universitas Muhammadiyah Sorong, 2025)
This study aims to explore the factors that influence patient decisions in choosing dr. Dian Beauty Clinic in Jember through a grounded theory approach. With a qualitative method, this study successfully identified three main dimensions that interact with each other: rational factors, emotional-social factors, and digital-education mediators. Data were collected through in-depth interviews with 19 active patients selected using purposive and snowball sampling techniques, with the criteria of having made at least two visits and being in the age range of 20-45 years. The research findings revealed that patient decisions are formed through a complex integration of objective considerations (procedure safety, price, and evidence of effectiveness) with subjective factors (reputation, convenience, and religious values). Digital media plays an important role as a catalyst, where 73% of informants stated that social media content and online features are the main considerations. Uniquely, local values such as sharia services and gender privacy are critical differentiators for 42% of patients. The study also found significant generational differences - younger patients (Gen Z/Millennials) are more influenced by digitalization, while generation X relies more on personal recommendations. The implications of this study highlight the importance of a holistic approach in beauty clinic management, which combines strict medical standards with personalized patient experience. These findings contribute to the development of a healthcare marketing model that is adaptive to the socio-cultural characteristics of Indonesian society, especially in the Jember area. Further research is recommended to test this model in more diverse geographic and demographic contexts.